An environmental justice assessment of public beach access in Miami, Florida. (August 2015) - Montgomery, Marilyn C.; Chakraborty, Jayajit; Grineski, Sara E.; Collins, Timothy W.
Abstract: The scope of empirical environmental justice (EJ) research has expanded beyond hazards exposure to scrutinize social inequities in access to amenities, but no prior study has examined the EJ implications of public beach access. Furthermore, quantitative research on white privilege is very scarce. To address these knowledge gaps, our study examines racial/ethnic and socioeconomic inequities in access to public beaches in the Miami metropolitan statistical area, Florida. Public beach accessibility is modeled with an innovative geospatial approach that involves population weighted distances to beach access sites. To assess EJ implications of public beach access for various racial/ethnic and socioeconomically vulnerable groups, spatial regression models are estimated using census tract-level data. Results indicate that beaches are more accessible to neighborhoods with a higher proportion of non-Hispanic Whites, while neighborhoods with higher percentages of Hispanics and socioeconomically disadvantaged residents have limited access. This study demonstrates the importance of assessing white privilege and access to environmental amenities in EJ research to better understand social inequities. Highlights: We examine environmental justice (EJ) implications of public beach accessibility. Public beach accessibility is modeled with geographic information science (GIS). We quantitatively investigate white privilege. Predominantly non-Hispanic White neighborhoods have easy access to public beaches. Mostly racial/ethnic minority neighborhoods have limited public beach access.